Investigation of the seasonal and local time variations of the high‐altitude sporadic Na layer (Nas) formation and the associated midlatitude descending E layer (Es) in lower E region. Issue 7 (28th July 2014) - Yuan, T.; Wang, Jihong; Cai, Xuguang; Sojka, J.; Rice, D.; Oberheide, J.; Criddle, N.
Abstract Recent studies have suggested that the major reservoir for the sporadic sodium layer (Nas) above 95 km in altitude is likely the sodium ion (Na+) within the sporadic E layer (Es) in the lower E region. However, theoretical and laboratory works have demonstrated that the metal ion's neutralization process is quite difficult above 100 km, while intensive neutral metal layers are consistently observed in the lower E region between 100 km and 125 km. In this paper, the multiyear observations of a Na lidar and an ionosonde at Utah State University (41.7°N, 111.8°W) and the nearby Bear Lake Observatory (41.9°N, 111.4°W) are utilized to understand their seasonal and local time variations. The comparison study between this set of the Nas and the nocturnal Nas observations in Beijing China (40.2°N, 116.1°E) reveals similar variations, but major differences are also noticed. To investigate the mechanism of these variations, the Hamburg Model of the Neutral and Ionized Atmosphere and the Climatological Tidal Model of the Thermosphere are utilized to simulate the ion vertical drift in the lower E region. The simulation shows that the lower E region is dominated by convergence of metal ions in summer, and ion diffusion prevails during winter. The tidal wind modulates the ion vertical drift speed and increases the likelihood of Es evolution at certain local times during the summer, while the tidal components of atmospheric density facilitate Nas formation by neutralizing the Na+ within the Es.